2013
DOI: 10.3168/jds.2013-7012
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the constitutive microflora of biofilms formed on whey reverse-osmosis membranes to individual cleaning steps of a typical clean-in-place protocol

Abstract: This experiment evaluates the effectiveness of individual steps of a clean-in-place protocol against the biofilm constitutive microflora isolated from the biofilms developed on whey reverse-osmosis membranes, aged 2 to 14 mo, under industrial processing conditions. The isolates used for the in vitro resistance studies included species of Bacillus, Enterococcus, Streptococcus, Staphylococcus, Micrococcus, Aeromonas, Corynebacterium, Pseudomonas, Klebsiella, and Escherichia. The 6 cleaning steps (alkali, surfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 29 publications
(34 reference statements)
1
40
0
Order By: Relevance
“…The increasing recovery of these species is maintained even after the CIP process (data not shown), suggesting these bacteria are resistant to different stressful conditions. Resistance to heat (pasteurization) and cleaning (CIP) processes might be linked to the ability of the microorganisms to form biofilms, as has been reported by many authors (Anand and Singh 2013;Flint et al 2002;Peng et al 2002). In this context, all E. faecalis strains analyzed in this work were able to form biofilms on polystyrene surfaces.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The increasing recovery of these species is maintained even after the CIP process (data not shown), suggesting these bacteria are resistant to different stressful conditions. Resistance to heat (pasteurization) and cleaning (CIP) processes might be linked to the ability of the microorganisms to form biofilms, as has been reported by many authors (Anand and Singh 2013;Flint et al 2002;Peng et al 2002). In this context, all E. faecalis strains analyzed in this work were able to form biofilms on polystyrene surfaces.…”
Section: Discussionsupporting
confidence: 50%
“…High genetic diversity was found among isolates recovered before and after pasteurization from all bacterial species, which further supports the view that pasteurization does not make a selection for certain genetic profiles. All microbial types identified in this work have already been reported to attach to stainless steel pipe surfaces (Anand and Singh 2013;Mattila et al 1990;Sharma and Anand 2002). The presence of microorganisms on dairy surfaces in postpasteurization lines is a cause of concern, as it may cause spoilage of processed dairy products and/or be involved in food safety issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dairy industry, biofouling may also result in serious quality issues for the filtered fluid and subsequent dairy products because of the presence of spore-forming or pathogenic bacteria on membranes (Burgess et al 2010;Anand et al 2014) and their concurrent microbial enzyme production (Raats et al 2011;Teh et al 2014). However, only a few studies described the microbial composition of biofilm detected on dairy processing membranes, and they have been limited to microscopy (Hassan et al 2010) or culture-based observations (Tang et al 2009;Tang et al 2010;Anand et al 2012;Anand and Singh 2013). Considering that the majority of bacteria in environmental samples are usually unculturable (Amann et al 1995), the use of culture-independent approaches, such as metagenomics, is essential.…”
Section: Introductionmentioning
confidence: 99%
“…For most dairy fluids, short-and long-term fouling results from the accumulation of proteins (Bégoin et al 2006) and minerals (Anand et al 2014) on membrane surfaces. However, concerns around bacterial adhesion warrant further investigation in the dairy industry because of the great resilience of biofilms exposed to cleaning procedures (Tang et al 2009;Hassan et al 2010;Anand et al 2012;Anand and Singh 2013;Anand et al 2014) and the high bacterial counts observed in filtered products (Anand et al 2012). Biofouling, through biofilm development, has been reported in desalination plants (Matin et al 2011;Khan et al 2013;Levi et al 2016) and membrane bioreactors (Ivnitsky et al 2007;Malaeb et al 2013;Vanysacker et al 2014b).…”
Section: Introductionmentioning
confidence: 99%